2020
DOI: 10.1167/iovs.61.14.4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Class I and IIb HDACs by δ-Opioid in Chronic Rat Glaucoma Model

Abstract: PURPOSE. This study determines if δ-opioid receptor agonist (i.e. SNC-121)-induced epigenetic changes via regulation of histone deacetylases (HDACs) for retinal ganglion cell (RGC) neuroprotection in glaucoma model. METHODS. Intraocular pressure was raised in rat eyes by injecting 2M hypertonic saline into the limbal veins. SNC-121 (1 mg/kg; i.p.) was administered to the animals for 7 days. Retinas were collected at days 7 and 42, post-injury followed by measurement of HDAC activities, mRNA, and protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Pupils were dilated with topical 0.5% tropicamide (Akorn, Lake Forest, IL, USA) and 2.5% phenylephrine HCL (Paragon BioTeck, Portland, OR USA). PERG recording of both eyes was performed simultaneously to investigate RGC function using the Celeris-Diagnosys system (Diagnosys, Lowell, MA, USA) according to a published protocol [ 43 , 44 ]. Briefly, mice were placed on Celeris-Diagnosys system equipped with a feedback-controlled heating pad for maintaining animal core temperature at 37 °C, and small lubricant eye drop (GenTeal Lubricant Eye Gel, Alcon, Ft. Worth, TX) was applied before recording to prevent corneal dryness.…”
Section: Methodsmentioning
confidence: 99%
“…Pupils were dilated with topical 0.5% tropicamide (Akorn, Lake Forest, IL, USA) and 2.5% phenylephrine HCL (Paragon BioTeck, Portland, OR USA). PERG recording of both eyes was performed simultaneously to investigate RGC function using the Celeris-Diagnosys system (Diagnosys, Lowell, MA, USA) according to a published protocol [ 43 , 44 ]. Briefly, mice were placed on Celeris-Diagnosys system equipped with a feedback-controlled heating pad for maintaining animal core temperature at 37 °C, and small lubricant eye drop (GenTeal Lubricant Eye Gel, Alcon, Ft. Worth, TX) was applied before recording to prevent corneal dryness.…”
Section: Methodsmentioning
confidence: 99%
“…One of the proposed mechanisms for the beneficial effects of delta-opioid agonism is epigenetic modification. Histone deacetylase activity has been positively correlated with glaucoma progression, and delta-opioid agonism was demonstrated to suppress this activity in ocular hypertensive animal models ( Zaidi et al, 2020 ). Modification of the epigenetic pathway has also been researched in non-retinal cells, including restoration of cells comprising the trabecular meshwork and Schlemm’s canal system ( Sharif, 2021 ).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Unfortunately, some patients under IOP-lowering therapy still see progression of the disease, which clearly indicates that better therapeutic options are needed to fully cure the disease. Studies have shown that multiple factors play key roles in RGC degeneration including activation of caspases [ 44 , 141 , 142 , 169 , 208 , 320 ], apoptosis [ 6 , 116 , 226 , 255 , 327 ], oxidative stress [ 56 , 143 , 150 , 198 , 219 , 228 , 272 ], ischemia and hypoxia [ 32 , 57 , 141 , 141 , 142 , 142 , 144 , 234 ], epigenetic changes [ 105 , 206 , 242 , 276 , 353 , 359 , 359 , 360 , 360 ], Crosson 2010 #975, [ 145 ], alteration in the levels of pro-inflammatory cytokines [ 1 , 312 , 316 , 341 , 352 , 357 ], and deprivation of neurotrophic factors [ 240 , 256 ]. There is another opinion with limited evidence, which suggests the neurodegeneration observed in glaucoma could be vascular.…”
Section: Adaptive Immunity and Glaucomamentioning
confidence: 99%